1095. The Value of Hardwiring Diagnostic Stewardship in the Electronic Health Record: Electronic Ordering Restrictions for PCR-Based Rapid Diagnostic Testing of Diarrheal Illnesses. (26th November 2018) - Marcelin, Jasmine R; Brewer, Charlotte; Beachy, Micah; Lyden, Elizabeth; Winterboer, Tammy; Hood, Lauren; Fey, Paul D; Van Schooneveld, Trevor
Abstract: Background: In 2015, the microbiology laboratory introduced a multiplex PCR test (FilmArray™ Gastrointestinal Panel (GIP)), replacing traditional stool culture. The GIP is faster and more sensitive than traditional stool culture, detecting 22 common viral, bacterial, and parasitic pathogens; but is significantly more expensive. The antimicrobial stewardship program (ASP) developed guidelines on test use and interpretation, recommending inpatient use only once per admission and not after hospital day 5. C. difficile test results from the GIP were not reported at any time. Methods: Inpatient GIP use was reviewed over one year and considered inappropriate if performed >3 days after admission or repeated. Noncompliance with ASP recommendations was common; no meaningful pathogens were detected upon review of all inappropriate GIP use. An inpatient GIP electronic order restriction was implemented in April 2017 eliminating the ability to order tests inappropriately. GIP testing outside the restriction could be approved by the microbiology lab director. We captured separate C. difficile testing rates as a counterbalance measure. We used Poisson regression models to compare the rate of GIP and C. difficile tests per month between Period 1 (July 2015–March 2017) and Period 2 (April 2017–March 2018) per 1, 000 patient-days (PD). Results: The restriction resulted in a 26% reduction in GIP ordering rates between the two periods (Table 1, Figure 1). Direct cost savings was approximately $63, 000. Table 1 shows changes in C. difficile test ordering rates during Periods 1 and 2. When including GIP tests that were ordered but not completed, potential GIP testing was reduced by 46% for a savings of $131, 000 (Figure 2). Only 42 test overrides were approved by the microbiology director since the intervention; of those only two were positive ( Cryptosporidium and Norovirus ). Conclusion: Diagnostic stewardship of GIP using guidelines and electronic ordering restrictions can lead to meaningful improvements in test appropriateness and reduction in cost and waste, demonstrating the value of ASP interacting with the microbiology laboratory. Disclosures: All authors: No reported disclosures.